Ability test of two algae Chlorella vulgares. Proscott and Navicual busiedtii. Kützing in reduction water salty excessive for river arabs - Al-Hussieny, Ahmed; Abed Alsada, Lamyia; Faiq, Abeer; Batah, Asraa; Abed, Ibrahim; Fauzy, Shoruk (Iraqi Journal of Science, 2023)
Different concentrations prepared 2,4,8,16,32 ppt from flow water to Shatt-Alarabby adding Chlorella vulgares and Navicual busiedtii as alone for eachconcentration. The results showed that the concentrations of salinity reduced to 0,1.78, 9.45, 15 ppt after 10 days, with removed percentage 100, 100, 77.75, 40.93,37.12 % respectively for Chlorella vulgares the cell numbers of Chlorella vulgaresreached to 58.123, 60.123, 69.712, 37.234, 30.546 ×104/ml comparing with thecontrol 55.652 ×104/ml while the absorbability of salinity reached to 0.378, 0.391,0.489, 0.231, and 0.192 nm comparing with 0.342 as control. The external cell wallof Chlorella vulgares was swelling at 32 ppt. the removal percentage of salinityreached to 100, 100, 75 , 66, 45 % for Navicual busiedtii with cell numbers reachedto 97.113, 120.903, 178.024, 231.112, 77.132 ×104/ml respectively comparing with91.362 ×104/ml as control, while the absorbability of salinity ranched to 0.354,0.367, 0.484 and 0.123 nm without change at cell wall of Navicual busiedtii.